👤

Proszę o szybką pomoc !!!!

Proszę O Szybką Pomoc class=

Odpowiedź :

Odpowiedź:

-(2x²+x)+2x²-x=-2x²-x+2x²-x=-2x A

-(2x²+x)+3x²+x=-2x²-x+3x²+x=x² D

-(2x²+x)+x²-2x=-2x²-x+x²-2x= -x²-3x A

-(x²-2x)+2x²-x=-x²+2x+2x²-x=x²+x A

-(x²-2x)+3x²+x=-x²+2x+3x²+x=2x²+3x R

-(x²-2x)+x²-2x=-x²+2x+x²-2x=0 Y

-(-2x²+3x)+2x²-x=2x²-3x+2x²-x=4x²-4x T

-(-2x²+3x)+3x²+x=2x²-3x+3x²+x=5x²-2x I

-(-2x²+3x)+x²-2x=2x²-3x+x²-2x=3x²-5x K

3x²-5x K

-2x A

2x²+3x R

5x²-2x I

-x²-3x A

4x²-4x  T

0  Y

x² D

x²+x   A

KARIATYDA

Szczegółowe wyjaśnienie:

On Studier: Inne Pytanie